HATE CRIMES: THE ULTIMATE ANATHEMATIC CRIMES - Nina Mollema; Charnelle van der Bijl (Obiter, 2014)
Hate crimes are grave offences that involve violations of human rights and humanitarian law. Hate crimes are offences which are motivated by bias or prejudice against a person based on their ethnicity, race, colour, sexual orientation, gender, handicap or religion. If one considers the severity of these crimes and the cumulative consequences thereof, it is evident that these crimes do not get as much concern as they should. The conduct in this type of crime targets groups of individuals based on their actual or perceived membership in a particular group. The crimes are profoundly influenced and driven by the collective action of its perpetrators, also members of a group, who regard themselves as superior. The interplay between individual action and group membership is central to these crimes in so far as this interplay engenders thorny questions of responsibility and punishment. This note intends to explore the manner in which South African and American criminal law give impetus to the criminalization of the above-mentioned collective wrongdoing. It is important to consider the handling of hate crimes in American society as South Africa has a similar history of racial discrimination to that in the United States. The first part of the note will delineate the concept of hate crime, while the second part will examine hate crimes from a South African as well as American criminal-law perspective. Lastly, the punishment of perpetrators of prejudice-motivated crimes is investigated as a final intervention in combating this manifestation in South Africa.